Car Brake Works as Indicator Tool - Sudarsono, Bambang; Hamid Nasrullah; Fanani Arif Ghozali; Aji Apri Setiawan (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2021)
Accidents caused by malfunctioning of the brake light system are increasing in line with the rise in road facilities. It provides space for drivers to drive vehicles quickly. To overcome this problem, a system that can signal the driver must rapidly identify the damaged brake lights. The purpose of this study was to produce a car brake indicator tool. This tool is an electronic device that functions to determine the brake light when one of the brake lights is off by automatically giving a signal on the car's dashboard. The method used to produce brake work indicator tools consists of designing, manufacturing, and testing. The testing process has been carried out through a lux meter, and the test variables include testing the use of electric current, voltage when the tool is working, and trying the performance of the device on the car. From testing this tool, the results obtained when the current usage of the tool is working, namely before the induction works of 2 amperes and when the induction works it is 0.5 amperes. The magnitude of the voltage when the device is used is 11.8 volts. Based on the experiments that have been carried out, there are no disturbances in the lighting system or other systems on the car when this tool is working. This tool can work well to provide convenience and comfort when driving by car. Based on the experiments that have been carried out, there are no disturbances in the lighting system or other systems on the vehicle when this tool is working. This tool can work well to provide convenience and comfort when driving by car. Based on the experiments that have been carried out, there are no disturbances in the lighting system or other systems on the vehicle when this tool is working. This tool can work well to provide convenience and comfort when driving by car.